Controls on Gas Emission Distribution on the Continental Slope of the Western Black Sea - Riedel, Michael; Hähnel, Line; Bialas, Jörg; Bachmann, Anna Katharina; Gaide, Stefanie; Wintersteller, Paul; Klaucke, Ingo; Bohrmann, Gerhard (Frontiers in Earth Science, 2021)
The continental slopes of the Black Sea show abundant manifestations of gas seepage in water depth of < 720 m, but underlying controls are still not fully understood. Here, we investigate gas seepage along the Bulgarian and Romanian Black Sea margin using acoustic multibeam water column, bathymetry, backscatter, and sub-bottom profiler data to determine linkages between sub-seafloor structures, seafloor gas seeps, and gas discharge into the water column. More than 10,000 seepage sites over an area of ~3,000 km2 were identified. The maximum water depth of gas seepage is controlled by the onset of the structure I gas hydrate stability zone in ~ 720 m depth. However, gas seepage is not randomly distributed elsewhere. We classify three factors controlling on gas seepage locations into depositional, erosional, and tectonic factors. Depositional factors are associated with regionally occurring sediment waves forming focusing effects and mass-transport deposits (MTDs) with limited sediment drape. Elongated seafloor depressions linked to faulting and gas seepage develop at the base between adjacent sediment waves. The elongated depressions become progressively wider and deeper towards shallow water depths and culminate in some locations into clusters of pockmarks. MTDs cover larger regions and level out paleo-topography. Their surface morphology results in fault-like deformation patterns of the sediment drape on top of the MTDs that is locally utilized for gas migration. Erosional factors are seen along channels and canyons as well as slope failures, where gas discharge occurs along head-scarps and ridges. Sediment that was removed by slope failures cover larger regions down-slope. Those regions are devoid of gas seepage either by forming impermeable barriers to gas migration or by removal of the formerly gas-rich sediments. Deep-rooted tectonic control on gas migration is seen in the eastern study region with wide-spread normal faulting promoting gas migration. Overall, gas seepage is widespread along the margin. Gas migration appears more vigorous in shallow waters below ~ 160 m water depth, but the number of flare sites is not necessarily an indicator of the total volume of gas released.